Novel Technique of Selective Stent Deployment in Complicated Thoracic Aortic Aneurysm. Issue 3 (1st July 2017) - Young, Allan; Kastner, Lauren; Vasquez, Javier
Abstract : A 72-year-old woman presented with a thoracic aortic aneurysm that was found to have increased from 5.1 cm to 7.1 cm. Due to the increase in size, the aortic aneurysm required endovascular repair. After deployment of a GORE C-TAG stent graft, a distal type 1 endoleak was still present, requiring deployment of another stent to achieve total coverage. The aorta had an angled anatomical variation often associated with type 1 endoleaks causing technical difficulty with conventional deployment of the graft. By employing a novel Parachute technique, the graft was selectively deployed at the distal end, and the position was adjusted to fit the angulation of the aorta, followed by selective deployment of the proximal end. This selective deployment allowed for the adjustment necessary to effectively cover the endoleak.